Les Lettres Chinoises by Ying Chen: Writing Exile and Epistolary Romance through non-dit - Tan, Xinyi (Alternative francophone, 2026)
This article examines Chinese Canadian author Ying Chen’s Les Lettres chinoises through the lens of non-belonging, translingual writing, and the poetics of the non-dit. Building on Rosalind Silvester’s concept of “non-belonging” and Roland Barthes’s notion of écriture blanche, it argues that Chen transforms neutrality and universalism into a translingual mode of meaning production grounded in silence, omission, and ambiguity. At the center of the novel lies a “double absence”: the suppression of Chinese in a text that paradoxically foregrounds it in its title, and the refusal to name the real cause of the couple’s estrangement. Through close readings of the novel’s epistolary form, its use of Chinese cultural imagery, and its multilingual references to Mandarin, Shanghainese, and French, this article demonstrates how the non-dit structures both the representation of exile and the unfolding of the love triangle. It further demonstrates that exile in Chen’s novel is not merely geographic, but also linguistic, affective, and psychological. Ultimately, Les Lettres chinoises reimagines non-belonging not as absence alone, but as a generative condition through which identity, desire, and memory are continuously negotiated.